2003
DOI: 10.1111/j.1445-5994.2003.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Australasian haematologist referral patterns to palliative care: lack of consensus on when and why

Abstract: In theory there is a willingness to refer to palliative care, however this has yet to be translated to day-to-day practice. This may be due to prognostication difficulties, logistical factors and medical concerns. Models of referral are suggested for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
3
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 12 publications
2
70
3
2
Order By: Relevance
“…24,25 This makes it difficult to identify natural transitions to palliative goals of care. 26,27 In addition to these three primary findings, several other patient characteristics were identified that were independently associated with late hospice enrollment. These include male sex, comorbidities, and nonwhite ethnicity.…”
Section: Discussionmentioning
confidence: 94%
“…24,25 This makes it difficult to identify natural transitions to palliative goals of care. 26,27 In addition to these three primary findings, several other patient characteristics were identified that were independently associated with late hospice enrollment. These include male sex, comorbidities, and nonwhite ethnicity.…”
Section: Discussionmentioning
confidence: 94%
“…However, surveys of clinicians have identified a willingness to refer such patients and engage more actively with palliative care. 23 In order to improve collaboration with hematology, palliative care services must also be proactive and flexible. 24 The impact of palliative care services among patients was reflected in the fivefold lower proportion of inpatient deaths occurring in ICU that had been previously referred to palliative care.…”
Section: Increasing Hematology Referrals To Palliative Carementioning
confidence: 99%
“…10 The decision to delay the transition from a curative to a palliative strategy until a very late stage of the disease is particularly realistic for the hematological setting, where malignancies are so persistently sensitive to innovative treatment strategies that end-oflife care is ineffectual or not offered at all. [11][12][13] This is why we have also included in our HC program the group of patients in advanced phase of their disease with an expected median survival of more than 3 months.…”
Section: Discussionmentioning
confidence: 99%